ANALISIS KETERBACAAN BUKU AJAR BAHASA JAWA KELAS IV SEKOLAH DASAR SE-KARESIDENAN MADIUN - Maruti, Endang Sri; Kurniawati, Rissa Prima (Paramasastra, 2018)
ABSTRACTOne of the problems that arise in learning the Java language is when a student must be able to understand the textbook content used by teachers in the classroom. Many words or sentences in the Java language textbook that is difficult for students to understand because it feels foreign so that students do not understand what the meaning of the word or sentence. Based on the results of preliminary observations, students of the sixth grade of elementary school are not able to master the content of the material in textbooks that should be used for fourth grade students of elementary school. Therefore, this study aims to find out how much textbooks and textbooks that have been used in SD in Madiun Residency with each class level. Data analysis method used is with Fry Graph and Klos technique. The result of the research shows that the area that has been using textbook that is in accordance with the level of legibility is the area of Madiun, Magetan and Ngawi, while the other three regions of Pacitan, Ponorogo, and Madiun Kota are not suitable because they are too high, And 8, that means the textbook is appropriate for the junior level.Key words: Analysis of textbooks legibility, Javanese language